Penerapan Augmented Reality (AR) Berbantuan Flash Card Pada Pembelajaran IPS - Sri Gustiani; Andriana Sofiarini; Sujarwo (STAI AL-AMIN, 2025)
This study aims to determine the completeness of social studies learning outcomes of grade V students of SD Negeri 60, Lubuklinggau City. The quasi-experimental research method with the design used is One Group Pre-test and Post-test. The population and sample in this study were grade V students of SD Negeri 60, Lubuklinggau City in the 2024/2025 Academic Year, totaling 53 students. Class V A was selected as a sample of 26 students using the random sampling method in determining the sample. The data collection technique used are observation, interviews, and tests. The data analysis technique used the t-test with the research results for the final test (post-test) at a significant level of a = 0.05 obtained tcount > ttable = (18,68 > 1,708) which means Ho is rejected and Ha is accepted. Thus, the hypothesis proposed in this study is accepted as true. so it can be concluded that student learning outcomes after implementing Augmented Reality (AR) assisted by Flash Cards in social studies learning in class V of SD Negeri 60 Kota Lubuklinggau in the 2024/2025 Academic Year are significantly complete.